피부건강 웰니스 프로그램이 웰니스지수 및 피부건강지표에 미치는 영향 - 김현준; Kim, Hyunjun (Journal of the Korean Society of Integrative Medicine, 2019)
Purpose : Wellness tourism is defined as travel for the purpose of promoting health and well-being through physical, psychological, or spiritual activities. The development and verification of a comprehensive wellness program for health care for workers is needed. The purpose of this study is to investigate the wellness and skin health effects of skin health programs in order to develop high-value health care services. Methods : The subjects were 15 middle-aged women who understood the research and volunteered and participated in the two-day skin health wellness program. Participants were measured to determine their wellness index and skin health twice: before and after participating in the program. Wellness index measures include comprehensive wellness, physical wellness, mental wellness, emotional wellness, social/cultural wellness, financial wellness, and environmental wellness. Skin health measurement items consisted of skin oil, skin water, skin pore, skin elasticity, skin wrinkle, and skin pigment. The skin wellness program included aerobic exercise, endurance exercise, functional food, cosmetics, herbal tea, massages, spa treatments, meditation, and marine leisure sports. The t-test analysis was used to compare the difference between wellness index and skin health measurement items before and after the program. Results : Among the wellness index items, the comprehensive wellness index (p<.05), mental wellness index (p<.05) and environmental wellness index (p<.05) showed statistically significant differences. Among skin health items, skin oil (p<.05), skin elasticity (p<.01) and skin wrinkle (p<.01) all showed statistically significant differences. There was no statistically significant difference in physical wellness, emotional wellness, social/cultural wellness, financial wellness, skin water, skin pore and skin pigment. Conclusion : This study confirmed that the two-day complex wellness program is an effective program for some items of wellness index and skin health.